Fatores associados a autopercepção de saúde em universitários do centro-oeste brasileiro - Fonsêca, Camila Vanzin Bonifácio (Universidade do Vale do Rio dos Sinos, 2023)
Objective: To investigate the factors associated with self-rated health in health students of a university in the Brazilian Midwest, in addition to estimating poor self-rated health in these students. Methodology: Cross-sectional study, university-based, of both genders, enrolled in health care courses at a university located in the Brazilian Midwest, State of Goiás, Brazil, in 2018. Self-rated health was assessed using a single question: “In general, how would you say your health is?”. Responses ranged from poor, fair, good, very good and excellent. For analysis purposes, the categories were dichotomously regrouped into fair/poor and excellent/very good/good. Associated factors included demographic, socioeconomic, academic, psychosocial, and behavioral aspects and use of health services. Bivariate analyzes were conducted using chi-square tests for linear trend and Pearson. Prevalence ratios and crude and adjusted mean ratios were estimated using Poisson regression with robust variance. Results: It was found that among the 2280 study participants, 342 (15%) had poor self-rated health. In the adjusted analysis, they remained associated with the outcome female gender (PR= 1.53; CI 95%: 1.20-1.95), low economic class (PR=;1.92 CI 97%: 1.47-2.50), students who failed (PR =;1.95 CI 95%:1.46-2.62), and who are in the last periods of the course (PR=1.371; CI 95%:1.04-1.81), low quality of life (PR =2.231; CI 95%:1.59-3.12), and mental health with very high psychological distress (PR=3.450; CI 95%:2.19-5.42). Conclusion: The present study demonstrated the prevalence of poor self-rated health in university students in the health area and an association with sociodemographic, academic and psychosocial factors. Due to these findings, interventions related to improving the perception of health in this group are recommended, which prioritize actions aimed at health promotion and prevention.
Keywords: Autopercepção de saúde; Saúde autorreferida; Universitários; Fatores de risco; Corte transversal; Self-rated health; Self-reported health; College students; Risk factors; Cross sectional; ACCNPQ::Ciências da Saúde::Saúde Coletiva